Qualification of main impacts on the inductive skinning process of copper wire bundles - Spreng, Simon; Borngraeber, Thorsten; Gläßel, Tobias; Franke, Jörg (ICEC 2016 - 28th International Conference on Electric Contacts, 2016)
Aside from the distinct contacting process, within the field of electric drives production, the quality of the isolation skinning process has to be assured. One promising technology in this context is the inductive skinning process, which utilizes skin and proximity effects occurring at high-frequency alternating currents. By the use of these physical impacts, the surface of insulated copper materials can be strongly heated up in short process times, leading to an extensive removal of the thermosetting insulation coatings. The following paper presents the results, which were experienced by using an inductive skinning machine with frequencies of 280 kHz. Here, insulated copper wire bundles serve as application example, whereby the number and size of copper wires, as well as the insulation type is varied. Subsequently, different technologies e.g. mechanical and magnetic crimping to perform the following contacting process are qualified and evaluated against each other.
CRIS-Team Scopus Importer:2023-03-07
Keywords: Electric drives manufacturing; Inductive skinning; Joining process